Organizational Climate and Job Satisfaction Among Workers in a Peruvian Company - Tinoco Plasencia, Christian Jairo (2024)
Organizational climate is a crucial factor that influences job satisfaction among workers in any organization. This research aims to describe the perceived levels of organizational climate and job satisfaction among workers in a Peruvian company and determine the relationship between both variables. This is a basic, non-experimental, and correlational quantitative study. The sample consists of 40 workers employed in a civil construction company in Lima, Peru, and is a census sample. Organizational climate and job satisfaction questionnaires were used to collect data, with 28 and 25 items, respectively. The results report that organizational climate and job satisfaction reached moderate levels, with 62.50% and 60.00%, respectively. Based on the obtained Spearman’s rho value of 0.755 and a p-value of 0.000 < 0.05, it was determined that there exists a significant and high direct relationship between the variables under study.